Analysis and Synthesis of Delta Operator Systems with Actuator Saturation - Yang, Hongjiu; Xia, Yuanqing; Geng, Qing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents basic research on delta operator systems (DOS) with actuator saturation. It proposes null controllable regions of delta operator systems, introduces the enlarging of the domain of attraction and analyzes the performance of DOSs subject to actuator saturation. It also discusses the domain of attraction on different systems in delta domain, and investigates the applications in complicated systems using delta operator approaches.
Introduction -- Estimation of Null Controllable Region -- Stabilization on Null Controllable Region -- Practical Stabilization on Null Controllable Region -- Estimation of the DoA and Disturbance Rejection -- A Lifting Technique for Sampling Periods -- Analysis for Nested Actuator Saturation -- Saturation-Dependent Lyapunov Function -- Monotonicity and Parametric Riccati Equation -- Semi-Global Stabilization with Regional Performance -- Maximizing Convergence Rate in the DoA -- Output Regulation via State Feedback Control -- Low Gain Feedback via Parametric Riccati Equations -- Stabilization for 2-D Systems -- Stability Analysis for High Frequency Systems -- Robust Control for Markov Jump Systems -- Robust Control for T-S Fuzzy Systems -- Fault Tolerant Control with Effectiveness Loss -- Stabilization for Markov Jump Delay Systems -- Stabilization for Periodic Sampling Systems -- Quantized Stabilization for NCSs.
Keywords: Control engineering; System theory; Control theory; Multibody systems; Vibration; Mechanics, Applied; Control and Systems Theory; Systems Theory, Control; Multibody Systems and Mechanical Vibrations